PENGARUH PERBANDINGAN IKAN KEMBUNG (Rastrelliger kanagurta) DENGAN SAYUR GONDA (Sphenoclea zeylanica Gaertner) TERHADAP KARAKTERISTIK BAKSO - Mayank Dini, Brogina; Trisna Darmayanti, Luh Putu; Suter, I Ketut (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 4 (2020): Jurnal ITEPA, 2020)
This research was conducted with the aim to determine the effect of comparison of mackerel with gonda vegetable on meatballs characteristics and get a comparison of mackerel with specific gonda vegetable that can produce meatballs with the best characteristics. This study uses a Completely Randomized Design (CRD) with treatment that is the comparison of mackerel with gonda vegetable consisting of 6 levels: 100%: 0%; 95%: 5%; 90%: 10%; 85%: 15%; 80%: 20%; 75%: 25%. Each treatment was repeated 3 times so that obtained 18 units. The data is then analyzed by analysis of variance and if the treatment influences the proposed variable then it is continued by Duncan. The results showed that the comparison of mackerel and gonda vegetable had a very significant effect on water content, ash content, fat content, protein content, carbohydrate content, total chlorophyll content, antioxidant capacity, color (scoring), texture, aroma, overall acceptance and no significant effect for texture, aroma and taste. Comparison of 80% mackerel and 20% gonda vegetables had the best characteristics, with 62.99% water content, 1.56% ash content, 1.28% fat content, 8.75% protein content, 25.43% carbohydrate content, 18.39% total chlorophyll content, antioxidant capacity 25.63%. Sensory properties obtained are color (rather green, rather like), texture (rather like), flavor (liked) and overall acceptance (like).